An Empirical Investigation into the Feasibility of a Smoked Fish Enterprise Utilising Liquid Smoke Technology in Central Maluku Regency - Tomasila, Mozes; Latuheru, Belianus P; Ismail, Suryanti R (Jurnal Manajemen Bisnis, 2023)
The purpose of this research is to analyze the feasibility of liquid smoked fish businesses, especially tuna and skipjack, by utilizing liquid smoke technology in Tulehu Village and Waai Village, Central Maluku Regency. To find out whether this liquid smoked fish business is worth running or not. The research used a survey method with direct interview techniques with liquid smoked fish business actors in Tulehu Village and Waai Village regarding the liquid smoked fish production process, marketing, sales and profits obtained. The data obtained was then analyzed for business feasibility from a financial aspect. The analysis technique used is using investment criteria including: Payback Period, Net Present Value, Internal Rate of Return (IRR), and Profitability Index as well as investment risk using sensitivity analysis. The results of this research show that the liquid smoked fish business in Tulehu village and Waai village is considered feasible because the financial aspect is considered to meet the investment assessment criteria, the rate of return on investment (Payback Period) is faster than the project plan, namely 5 years, the Net Present Value has positive value, the Internal Rate of Return is above the expected profit level, and the Profitability Index /Benefit Cash Ratio Ratio is greater than oneKeywords: Feasibility of liquid smoked fish business, Payback Period, Net Present Value, Internal Rate of Return, Profitability Index /Benefit Cash ratio Ratio is greater than one